2012
DOI: 10.1128/mcb.06130-11
|View full text |Cite
|
Sign up to set email alerts
|

Proteins Associated with the Exon Junction Complex Also Control the Alternative Splicing of Apoptotic Regulators

Abstract: Several apoptotic regulators, including Bcl-x, are alternatively spliced to produce isoforms with opposite functions. We have used an RNA interference strategy to map the regulatory landscape controlling the expression of the Bcl-x splice variants in human cells. Depleting proteins known as core (Y14 and eIF4A3) or auxiliary (RNPS1, Acinus, and SAP18) components of the exon junction complex (EJC) improved the production of the proapoptotic Bcl-x S splice variant. This effect was not seen when we depleted EJC p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
142
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 119 publications
(158 citation statements)
references
References 80 publications
(104 reference statements)
14
142
1
1
Order By: Relevance
“…In agreement with its presumed role in pre-mRNA splicing, Acinus has also been identified as a component of functional spliceosomes (Rappsilber et al 2002;Zhou et al 2002). Additionally, Acinus regulates the splicing of a subset of genes involved in apoptosis in human cells (Michelle et al 2012) and has been proposed to couple Retinoic acid mediated transcription and splicing . Interestingly, Acinus, alongside the EJC, is required for definition and excision of neighboring introns in Drosophila (Hayashi et al 2014;Malone et al 2014).…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…In agreement with its presumed role in pre-mRNA splicing, Acinus has also been identified as a component of functional spliceosomes (Rappsilber et al 2002;Zhou et al 2002). Additionally, Acinus regulates the splicing of a subset of genes involved in apoptosis in human cells (Michelle et al 2012) and has been proposed to couple Retinoic acid mediated transcription and splicing . Interestingly, Acinus, alongside the EJC, is required for definition and excision of neighboring introns in Drosophila (Hayashi et al 2014;Malone et al 2014).…”
Section: Introductionmentioning
confidence: 78%
“…In mammalian cells, knockdown of EJC core proteins results in widespread alternative splicing changes, with similar changes in splicing observed upon knockdown of different EJC core components, yet displaying differences with down-regulation of other splicing factors that are not components of the EJC . A role for EJC components in the regulation of splicing of apoptotic regulators has also been reported (Michelle et al 2012). EJCs have been shown to multimerize with one another and form higher-order complexes containing in particular numerous SR proteins, leading to a model whereby EJCs and SR proteins could work in cooperation to promote mRNA packaging and compaction, affecting pre-mRNA splicing (Singh et al 2012).…”
Section: Eif4a3-dependent and Independent Splicing Events Regulated Bmentioning
confidence: 97%
“…The splicing changes depend on EJC core integrity A previous study showed that individual EJC components seem to preferentially associate with the Bcl-x premRNA to regulate its alternative splicing, probably independently of EJC core integrity [32]. Therefore, we have examined whether the EJC-dependent splicing events identified in this study require EJC core.…”
Section: Widespread Splicing Changes Are Identified In Ejc Knockdownmentioning
confidence: 84%
“…Several studies before have indicated that the EJC protein can regulate splicing in different species [27][28][29]31,32]. However, these studies only focused on a specific set of candidate genes.…”
Section: Resultsmentioning
confidence: 99%
“…Once clamped onto mRNA, the tetrameric core acts as a platform to recruit multiple factors conferring different functions to the EJC as mRNA progresses from splicing to translation. Notably, the EJC contributes in regulating the splicing of specific transcripts (8)(9)(10) and participates in mRNA transport (11). The EJC also plays a major role in nonsense-mediated mRNA decay (NMD) that triggers the decay of aberrant mRNAs containing a premature termination codon (12).…”
mentioning
confidence: 99%